Suitability of young rubber trees for the wood-based industry - Hong L T; Gan L T (In: Ensuring Sustainability and Competitiveness of the NR industry: Proceedings of the Rubber Growers' Conference, 17-19 July 1995, Kuala Lumpur, Malaysia, pp. 309-317., 1995)
Rubberwood is normally derived from 25 to 30-year-old trees when the trees are cut during replanting. The demand for the timber by the rubberwood processing industry is tremendous and coupled with the reduction in the replanting of rubber that the country is experiencing now, there could be a shortfall in the supply of the timber in the coming years. One way to overcome this projected shortfall is to plant and harvest the trees at a younger age to supply those industries that do not need large diameter logs, for example, the panel products factories and some furniture mills. Rubberwood derived during replanting is suitable for use by the wood processing industry even though there are inherent problems because of the presence of tension wood and juvenile wood. The properties and processing characteristics of rubberwood of ages 3, 8 and 14 years of PB 260 and 8 and 24 years of RRIM 600 were assessed in this study. An average sawn timber recovery of about 35;was obtained for trees of ages 8 and 14. For the 3-year-old trees a sawn timber recovery of about 23;was obtained and in general was of lower quality because of the higher intensity of knots and a higher percentage of wane. In general the properties of timber from ages 8 and 14 did not differ much from those of 25 to 30-year-old trees. Timber from 3-year-old PB 260 are of lower density, more prone to distortion during drying and less amenable to the application of finishes. Medium density fibreboard (MDF) made from timber of all the age groups met Type 300 of the Japanese Standard (JIS A5906-1983). Therefore rubberwood of 8 and 14 years' old of PB 260 and 8-year-old RRIM 600 do not differ significantly from those of 25 to 30-year-old trees, whereas 3-year-old rubberwood of PB 260 because of the differences in the wood properties are more suitable for the manufacture of panel products such as MDF.
Keywords: Rubberwood industry